دلالة أدوات الشرط - البب, إبراهيم; بابو, غياث (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول هذا البحث البنية الدلالية لأدوات الشرط لدى النحويين والبلاغيين ، فبدأ بالإشارة إلى ما يوحيه مصطلح الشرط لدى اللغويين ، ثم تحدث عن أدوات الشرط الجازمة ، وبيّن الدور الدلالي الذي تقوم به كل أداة على حدة ، والدلالات التي تفرزها بمقتضى السياق اللغوي ، وبعد ذلك انتقل إلى أدوات الشرط غير الجازمة ، وبيّن دلالة كل أداة . ويهدف هذا البحث إلى استجلاء الفروق الدلالية بين أدوات الشرط من حيث الاستعمال اللغوي في التركيب الكلامي ، بحيث لو استعملت أداة مكان أخرى لتغيّر المعنى الدلالي لهذا التركيب . This research deals with the semantic structure of conditional articles as seen by grammarians and rhetorics. It starts with the use of the term as used by the linguists, and then it talks about the conditional articles. It shows the semantic role that each one play and the signification they produce in term of context. Then the paper explain the non-conditional articles. The aim of this research is explaining the semantic differences between the articles.